The Impact of Financial Technology and Virtual Customer Service on Customer Satisfaction - Mentari, Theresia; Setiawan, Ricky Yunisar; Wiriatmaja, Nuraini Ulya; Hutauruk, Joseph Reynaldo; Muhyiansyah, Ahmad Rafli; Rahman, Nita (IJBLE Scientific Publications Community Inc., 2024)
This study was conducted to examine the effect of Financial Technology, Virtual Customer Service on Customer Satisfaction. This study uses a quantitative approach using primary data obtained from the results of a questionnaire and measured using a Likert scale. The population in this study were BRI Unit Cilik Riwut customers who used Financial Technology and Virtual Customer Service. The sample used in this study are 177 respondents who were determined using the Nonprobability Sampling method with Purposive Sampling type. This study uses the PLS-SEM analysis method which is processed with the SmartPLS 3.2.9 program. The results of this study indicate that Financial Technology partially has a positive effect on Customer Satisfaction and Virtual Customer Service partially have a positive effect on Customer Satisfaction. It is expected to add other variables and indicators that can affect customer satisfaction in order to obtain new and accurate research results.